A new species of Leptoplectus Casey from Ryukyu Islands, Japan, with comments on morphology of integumental structures in Euplectitae (Coleoptera, Staphylinidae, Pselaphinae) - Jałoszyński, Paweł; Nomura, Shûhei (Zootaxa, 2021)
Leptoplectus kijimunaa Jałoszyński & Nomura, sp. n. is described, based on a series of specimens collected on Okinawa Island, Japan. Morphological structures of the new species are illustrated in detail and compared to known characters of all remaining 14 congeners. As the diagnosis of Leptoplectus remains unclear, character variability within known species is discussed. It is concluded that within Palaearctic region, the bilobed labrum is a reliable character to distinguish this genus from other Euplectini. The placement of Labroplectus Kurbatov, treated as incertae sedis within the tribe Trichonychini in the latest edition of the Catalogue of Palaearctic Coleoptera, is verified and it is concluded that it should be maintained in Euplectini. An identification key to genera of northeastern Asian Euplectini is given. We also comment on outdated and inaccurate morphological nomenclature still broadly used in descriptions of new Pselaphinae taxa.